Bound by debt: Nutmeg trees and changing relations between farmers and agents in a Moluccan agroforestry systems - Messalina Lovenia Salampessy; Indra Gumay Febryano; Dini Zulfiani (Forestry Faculty, Universitas Hasanuddin, 2017)
Agroforestry is a land management system long practiced by communities in the Moluccas. The practice is commonly known as